2007
DOI: 10.4161/hv.3.5.4376
|View full text |Cite
|
Sign up to set email alerts
|

Anticapsular Polysaccharide IgG Concentrations in Mexican Children Formerly Immunized with Haemophilus Influenzae b Prp-T Vaccine

Abstract: Background: In 1999 H. influenzae b (Hib) PRP-T vaccine was introduced into primary immunization schedule in Mexico. There have been no studies evaluating antibody response after widespread immunization in our country. It is now recognized that Hib conjugates induce significant initial antibody levels that in some cases wane over time. This study relies on the measurement of IgG serum antibody concentrations to Hib capsular polysaccharide (PS) and is interpreted in the light of the accepted levels ≥0.15 mg/mL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Recent serological evidence has shown that the pentavalent vaccination in a well defined cohort of children between the ages of 7 and 93 months, demonstrated serum IgG concentrations >0.15 mg/ml. 28 These serological titers have been shown to confer protection against Hib invasive disease. 28 Therefore, the purpose of our study was to define the leading pathogens causing community-acquired meningitis (beyond the neonatal period) in a pediatric population in a major referral pediatric hospital in Mexico City.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent serological evidence has shown that the pentavalent vaccination in a well defined cohort of children between the ages of 7 and 93 months, demonstrated serum IgG concentrations >0.15 mg/ml. 28 These serological titers have been shown to confer protection against Hib invasive disease. 28 Therefore, the purpose of our study was to define the leading pathogens causing community-acquired meningitis (beyond the neonatal period) in a pediatric population in a major referral pediatric hospital in Mexico City.…”
Section: Discussionmentioning
confidence: 99%
“…28 These serological titers have been shown to confer protection against Hib invasive disease. 28 Therefore, the purpose of our study was to define the leading pathogens causing community-acquired meningitis (beyond the neonatal period) in a pediatric population in a major referral pediatric hospital in Mexico City. The causative organisms found in a particular region vary with the patient's age and general health, and with the immunization status of the community.…”
Section: Discussionmentioning
confidence: 99%
“…1). A similar trend was seen for age-stratified sera from Mexico City (13). In contrast, the GMCs of sera from Guadalajara increased in an age-dependent manner ( Table 2).…”
mentioning
confidence: 50%
“…PSAB-90 serum was used as a quality control. Data for IgG concentrations from Mexico City sera have been previously described (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation